The jarabe Mixteco, folkloric icon of Oaxaca state (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The Jarabe Mixteco is a compendium of sounds and joyful dances that has positioned itself as the representative dance of the Mixtec region due to the expectation and acceptance that it has caused in the national and international public. The seven sounds that compose it come from the popular folklore of regional community celebrations prior to the 20th century, the dance choreographies refer to representations of animals that are part of the daily life of mixtec peoples and also symbolize the process of falling in love between couples (man and woman). The clothing used in the presentation of this dance has shapes, colors, materials and symbols that express the native identity. The Jarabe Mixteco has played the role of ambassador of mixtec culture and the state of Oaxaca in all the places where it has been presented, this dance has had worldwide projection through its presentation at the “Guelaguetza” dance festival. The Jarabe Mixteco has become an icon of mixtec folklore as it is linked to the history, activities and practices of the population; for this reason, citizens, government authorities, cultural and academic organizations have been in charge of investigating, compiling, presenting, preserving and disseminating the cultural legacy of this dance.
Keywords: Photography; dance; mixtec; folklore; Mexico